A pH Responsive Redox Hydrogel for Electrochemical Detection of Redox Silent Biocatalytic Processes. Control of Hydrogel Solvation. Issue 4 (12th February 2015) - Contin, Andrea; Frasca, Stefano; Vivekananthan, Jeevanthi; Leimkühler, Silke; Wollenberger, Ulla; Plumeré, Nicolas; Schuhmann, Wolfgang; Rees, Neil V.
Abstract The control of bioelectrocatalytic processes by external stimuli for the indirect detection of non‐redox active species was achieved using an esterase and a redox enzyme both integrated within a redox hydrogel. The poly(vinyl)imidazole Os(bpy)2Cl hydrogel displays pH‐responsive properties. The esterase catalysed reaction leads to a local pH decrease causing protonation of imidazole moieties thus increasing hydrogel solvation and mobility of the tethered Os‐complexes. This is the key step to enable improved electron transfer between an aldehyde oxidoreductase and the polymer‐bound Os‐complexes. The off‐on switch is further integrated in a biofuel cell system for self‐powered signal generation.